Acolhimento, cogestão e apoio institucional : o saber da experiência - Silva, Mônica Vilchez da (Universidade Federal de São Carlos, 2016)
Embracement, Comanagement and Institutional Support are three concepts arisen while the Brazilian National Health System (SUS) was being developed, more than a decade ago. These concepts take part in guidelines of policies implemented by the Brazilian Health Department as well as in some of the routines of managers and health workers. The National Policy for Humanization – PNH (2003), a pioneer method regarding Institutional Support – and the National Policy of Primary Health Care (2012) – have both embraced in their official guidelines these technologies that are the expression of a wish to transform the dominant models that organize both management and health production. In view of the transforming power inherent to these devices, we have carried out a descriptive case study with a qualitative approach. This case study intends to analyze conceptions and routines produced by municipal managers and Primary Health Care workers taking part in the Program for Improvement of Access and Quality (PMAQ) and the institutional support group that was created in 2012, in a municipality of the Third Department of Regional Health (DRSIII) in the State of São Paulo. We have employed scientific productions including some capital works in the field of Brazilian Health Care, that depict experiences which are not in keeping neither with the neoliberal program nor an understanding of how micropolitics actually funcions in health work. We conducted two interviews with managers, four focal groups with health workers and one focal group with the municipal group of institutional support. To conduct the analysis of these interviews and focal groups we have employed the thematic and categorial content developed. After concluding the analysis we have observed an intense production in those groups. Embracement has produced four categories, and it has also brought to light the fact that their routines and practices consisted in a model focused on the medical consultation. The reception screens the users, then the nursing team take care the procedures prior to the medical consultation that in a practical sense, have little in common with the concept of embracement. There are other practices such as the nursing consultation and group reunions (if conducted by the workers themselves) that make a difference in the daily routine of the health unity. For the nurses, comanagement has produced five categories, and have also brought to light new ways of coordinating as well as new relations of power. In this municipality there are different spaces of management and meetings for the health teams which have been incorporated to the daily schedule. These spaces may be reevaluated so that they could function in a less taylorist and more democratic in which workers and health managers could take part. The Institutional support produced five categories which have proven to be an experience linked to procedures which are rooted on the professional developement of worker and have a direct connection to their expertise. The methodology employed by the support group was built on its own actions, creating an interplay between contract, demand and supply. The supporter's interventions are always questioned both by those who give and receive support. In spite of all the challenges and the cristallyzed notions about the subject, we consider this experience to be a very innovative one: it holds on for more than a decade to practices that have been recognized as the force that moves forward a model of health care that is defending life.
Keywords: Acolhimento; Cogestão; Apoio institucional; Humanização; Atenção primária; Embracement; Comanagement; Institutional support; Humanization; Primary health care; CIENCIAS DA SAUDE::ENFERMAGEM